The efficacy and safety of proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors combined with statins in patients with hypercholesterolemia: a network meta-analysis - Liu, Dong; Zhang, Jin; Zhang, Xiaoyu; Jiang, Fengli; Wu, Yiping; Yang, Beibei; Li, Xinghuan; Fan, Xiongxiong; Li, Han; Sun, Yu; Gou, Ruijie; Wang, Xinyu (Frontiers in Cardiovascular Medicine, 2024)
Background In recent years, the position of PCSK9 inhibitors as adjuvant therapy to statins in guidelines has further improved. However, there remained a dearth of direct comparative studies among different PCSK9 inhibitors. Therefore, this study aimed to conduct a network meta-analysis to evaluate the efficacy and safety of different PCSK9 inhibitors combined with statins. Methods A comprehensive literature search was conducted from the study's inception to 12 November 2023, encompassing multiple online databases including PubMed, Embase, Cochrane Central, Web of Science, and ClinicalTrials.gov to obtain relevant randomized controlled trials. Frequentist network meta-analysis was employed to compare the efficacy and safety of different PCSK9 inhibitors. The efficacy endpoints were low-density lipoprotein cholesterol (LDL-C), apolipoprotein B (ApoB), and lipoprotein (a) (Lp(a)). The safety endpoints were any adverse events (AE), severe adverse events (SAE), AE leading to treatment discontinuation, and injection-site reaction. Results Compared with placebo and ezetimibe, all PCSK9 inhibitors demonstrated significant reductions in LDL-C levels. Notably, evolocumab exhibited the most pronounced effect with a treatment difference of −63.67% (−68.47% to −58.87%) compared with placebo. Regarding dosage selection for evolocumab, the regimen of 140 mg Q2W (−69.13%, −74.55% to −63.72%) was superior to 420 mg QM (−61.51%, −65.97% to −57.05%). Based on rankings and P-scores analysis, tafolecimab 150 mg Q2W demonstrated superior efficacy in reducing ApoB levels (−61.70%, −84.38% to −39.02%) and Lp(a) levels (−43%, 30%, −68%, 81% to −17%, 79%). Furthermore, the safety profile of PCSK9 inhibitors was favorable with no increase in the incidence of AE, SAE, or AE leading to treatment discontinuation; however, alirocumab, inclisiran, and tafolecimab may potentially entail a potential risk associated with injection-site reactions. Conclusion Compared with placebo and ezetimibe, PCSK9 inhibitors can significantly reduce LDL-C, ApoB, and Lp(a) when combined with statins to treat hypercholesterolemia. Furthermore, PCSK9 inhibitors and ezetimibe exhibit similar safety profiles. Systematic Review Registration [PROSPERO], identifier [CRD42023490506].